Silicon-containing aromatic acetylene resin-based composite material and preparation method and application thereof
By combining silicon-containing aromatic resin with surface-treated hollow glass microspheres to form composite materials, the problem of existing resin-based composite materials not durable under high temperature conditions is solved, and the high-temperature thermal insulation materials used in the aerospace field are realized.
Patent Information
- Application Number
- CN202010082012.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-02-06
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-02-06
AI Technical Summary
Existing resin-based composite materials are not durable under high temperature conditions and cannot meet the needs of higher temperature conditions in the fields of aerospace and other fields.
Silicon-containing aromatic resin is used as the resin matrix and combined with the surface-treated hollow glass microspheres to form a silicon-containing aromatic resin-based composite material. The resin matrix of the material includes unmodified and modified silicon-containing aromatic resins, and the surface treatment of hollow glass microspheres includes increasing hydroxyl content and the use of silane coupling agents.
The composite material can withstand high temperatures of 500°C, has excellent mechanical properties, low density and low thermal conductivity, and is suitable for thermal insulation materials in aerospace and other fields.
Smart Images

Figure CN113214608B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-containing aromatic acetylene resin-based composite material and a preparation method and application thereof. Background Art
[0002] During high-speed and long-distance flight, the surface of the aircraft needs to withstand very high temperatures and very large airflow impacts. The increase in flight distance also causes it to experience more severe aerodynamic heat and large overload and other complex environments. In order to ensure the continuous and normal operation of the internal systems of the aircraft, the thermal insulation material used in its surface layer is required to have high temperature resistance, low density, low thermal conductivity and high mechanical strength.
[0003] However, among the existing thermal insulation composite materials, although aerogel thermal insulation materials have good thermal insulation effects, their mechanical properties are poor and they cannot play a load-bearing role; multi-layer thermal insulation materials can well isolate the internal and external heat flow environment of the spacecraft through the structural design of each layer, but their preparation process is complicated; resin-based composite materials have the characteristics of high specific strength, high specific modulus, and good overall molding, and are widely used in various aerospace vehicles. The relevant literature on representative resin-based composite materials is as follows:
[0004] In 2012, Zhu et al. [Zhu B, Ma J, Wang J, et al. Journal of Reinforced Plastics & Composites. 2012, 31(19): 1311-1326.] used four different types of hollow glass microspheres (HGM) to systematically study the relationship between HGM volume fraction (10%-60%) and density (0.125-0.60 g·cm- 3 ) on the thermal insulation, dielectric and compression properties of hollow glass microsphere / epoxy resin composites. The results showed that with the increase of HGM volume fraction or the decrease of HGM density, the thermal conductivity, dielectric constant and dielectric loss, compression modulus and compression strength of the composites tended to decrease. In the same year, Hu et al. [Yan Hu, Riguo Mei, Zhenguo An, et al.. Composites Science & Technology, 2013, 79(5): 64–69.] prepared hollow glass microsphere / silicone rubber composites with different contents of broken hollow glass microspheres. When the mass percentage of hollow glass microspheres was 16.9% and all hollow glass microspheres were intact, the density of the composite was 0.79 g·cm -3 , tensile strength is 0.61MPa, elongation at break is 80%, thermal conductivity is 0.167W·m -1 ·K -1 .
[0005] In 2015, Cheng Haiming et al. [Cheng Haiming, Xue Huafei, Hong Changqing et al. Preparation and thermal insulation performance of a new type of low-density and low-thermal conductivity carbon / phenolic composite material. Rare Metal Materials and Engineering, 2015(S1):478-481.] used high-porosity phenolic resin to impregnate low-density, low-thermal conductivity chopped carbon fiber skeleton to prepare a new type of carbon / phenolic composite material. The density of the composite material is 0.25-0.43g·cm -3 The thermal conductivity is between 0.20-0.35W·m -1 ·K -1 , but its compressive strength along the thickness direction is 0.6-1.8MPa.
[0006] In 2018, Zhang Ning et al. [Zhang Ning. Preparation and thermal insulation performance of lightweight and high-strength thermal insulation composite materials. Harbin Engineering University. Master's thesis, 2018.] prepared hollow microsphere / epoxy resin-based composite materials. The comprehensive performance was the best when the volume fraction of hollow microspheres was 30%, and its density was 0.91 g·cm -3 , compression strength is 83.8MPa, thermal conductivity is 0.1676W·m -1 ·K -1 .
[0007] In the above literature, the resistant temperature of the composite material with phenolic resin, epoxy resin or silicone rubber as the resin matrix is only 300°C, which cannot adapt to the higher temperature conditions in the fields of aerospace and aviation. Therefore, it is urgent to prepare a resin-based composite material that can adapt to the higher temperature conditions in the fields of aerospace and aviation. Summary of the invention
[0008] The technical problem to be solved by the present invention is to overcome the problem that the composite materials with phenolic resin, epoxy resin or silicone rubber as the resin matrix in the prior art cannot adapt to the higher temperature conditions in the fields of aerospace and aviation, and to provide a silicon-containing aromatic acetylene resin-based composite material and its preparation method and application.
[0009] The present invention solves the above technical problems through the following technical solutions:
[0010] The present invention provides a silicon-containing aromatic acetylene resin-based composite material, wherein the silicon-containing aromatic acetylene resin-based composite material comprises a resin matrix and surface-treated hollow glass microspheres;
[0011] The resin matrix is an unmodified silicon-containing arylacetylene resin and / or a modified silicon-containing arylacetylene resin; the modified silicon-containing arylacetylene resin is a silicon-containing arylacetylene resin modified with aryl dipropargyl ether, and the mass percentage of the aryl dipropargyl ether in the modified silicon-containing arylacetylene resin is w, 0<w≤50%;
[0012] The mass percentage of the resin matrix in the silicon-containing aromatic acetylene resin-based composite material is 50%-75%;
[0013] The mass percentage of the surface-treated hollow glass microspheres in the silicon-containing aromatic acetylene resin-based composite material is 25%-50%.
[0014] In the present invention, the mass percentage of the resin matrix in the silicon-containing aromatic acetylene resin-based composite material is preferably 50%-70%, such as 58% or 60%.
[0015] In the present invention, the unmodified silicon-containing arylacetylene resin may be a conventional unmodified silicon-containing arylacetylene resin in the prior art, for example, prepared by referring to the preparation method in paragraph
[0044] of the specification of patent document CN102649838A.
[0016] In the present invention, the aryl dipropargyl ether may be a conventional aryl dipropargyl ether used for modification of silicon-containing arylacetylene resins, preferably one or more of bisphenol A dipropargyl ether, 4,4'-bisphenol fluorene dipropargyl ether and 4,4'-diphenyl ether dipropargyl ether, more preferably bisphenol A dipropargyl ether.
[0017] In the present invention, the mass percentage of the aryl dipropargyl ether in the modified silicon-containing arylacetylene resin is preferably 10%-30%, for example 20%.
[0018] In the present invention, the mass percentage of the surface-treated hollow glass microspheres in the silicon-containing aromatic acetylene resin-based composite material may be 30%, 32% or 35%.
[0019] In the present invention, the surface-treated hollow glass microspheres can be the surface-treated hollow glass microspheres conventionally used in the preparation of resin-based composite materials in the prior art, which are generally prepared according to the following treatment methods: (1) treating the hollow glass microspheres to increase the hydroxyl content on their surfaces; and (2) treating with a silane coupling agent so that one end of the silane coupling agent is connected to the hydroxyl groups on the surfaces of the hollow glass microspheres.
[0020] The conventional operation of step (1) is as follows: the hollow glass microspheres are dispersed in a treatment solution I and soaked for 0.5-2 hours, for example, 1 hour, and then washed with deionized water, solid-liquid separated until the filtrate is neutral, and dried to obtain hollow glass microspheres I; wherein the treatment solution I is prepared by 90wt%-98wt% concentrated sulfuric acid and 20wt%-40wt% hydrogen peroxide in a volume ratio of (2-4):1.
[0021] The hollow glass microspheres are preferably of model VS5500, and are manufactured by 3M China Ltd.
[0022] The mass of the hollow glass microspheres and the volume of the treatment solution I are preferably 1:(3-5), for example 1:4, in units of g / mL.
[0023] Preferably, the treatment solution I is prepared from 98 wt % concentrated sulfuric acid and 30 wt % hydrogen peroxide in a volume ratio of 3:1.
[0024] The drying temperature is preferably 90-110°C, for example 100°C.
[0025] The conventional operation of step (2) is as follows: the aforementioned hollow glass microspheres I are dispersed in a treatment solution II, a silane coupling agent is added, and the mixture is stirred at 25-65° C. for 2-6 hours, solid-liquid separation is performed, and the mixture is dried; wherein the treatment solution II is prepared from water, acetic acid and ethanol in a volume ratio of 1:(1-3):(7-11), and the mass of the silane coupling agent accounts for 0.5%-5% of the mass of the hollow glass microspheres.
[0026] The ratio of the mass of the hollow glass microspheres to the volume of the treatment solution II is preferably 1:(7-9), for example 1:8, and the unit is g / mL.
[0027] Preferably, the treatment solution II is prepared from water, acetic acid and ethanol in a volume ratio of 1:2:9, and the mass of the silane coupling agent accounts for 2% of the mass of the hollow glass microspheres.
[0028] The silane coupling agent used may be a conventional silane coupling agent for connecting to the hydroxyl groups on the surface of hollow glass microspheres, preferably one or more of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-(methacryloxy)propyl trimethoxysilane and ethynyl triethoxysilane. The product model of the γ-aminopropyl triethoxysilane may be KH-550. The product model of the γ-glycidyloxypropyl trimethoxysilane may be KH-560. The product model of the γ-(methacryloxy)propyl trimethoxysilane may be KH-570. The ethynyl triethoxysilane (TEOAS) may be prepared with reference to patent US 20120190549.
[0029] The stirring may be performed at 40° C. The stirring time may be 4 hours.
[0030] The drying temperature is preferably 90-110° C., such as 100° C. The drying time is preferably 10-14 h, such as 12 h.
[0031] In the present invention, the silicon-containing aromatic acetylene resin-based composite material preferably contains chopped fibers and / or fiber cloth.
[0032] The length of the chopped fibers is generally 5-50 mm, preferably 20-40 mm.
[0033] The chopped fibers may be one or more of high silica glass fibers, quartz glass fibers and carbon fibers. The carbon fibers may be T700 carbon fibers from Toray Industries, Ltd. of Japan. The quartz glass fibers may be B-type quartz fibers from Hubei Feilihua Quartz Glass Co., Ltd.
[0034] The chopped fibers may be conventional surface-treated chopped fibers in the prior art, and the treatment method is generally as follows: the chopped fibers are dispersed in an acetone solution, ultrasonically cleaned for 1-3 hours, repeated for more than 3 times to remove the surface sizing agent, and then dried. The ultrasonic cleaning time is preferably 1-1.5 hours. The drying temperature is preferably 85-95°C, such as 90°C. The drying time is preferably 3-5 hours, such as 4 hours.
[0035] The mass percentage of the chopped fibers in the silicon-containing aromatic acetylene resin-based composite material may refer to the mass percentage of the chopped fibers in the resin-based composite material, and is preferably 5%-25%, such as 8% or 12%.
[0036] The fiber cloth may be a conventional fiber cloth in the prior art, and may be one or more of high silica glass fiber cloth, quartz glass fiber cloth and carbon fiber cloth. The carbon fiber cloth may be T300 carbon fiber cloth from Toray Industries, Ltd. of Japan. The quartz glass fiber cloth may be quartz fiber cloth from Hubei Feilihua Quartz Glass Co., Ltd.
[0037] The mass percentage of the fiber cloth in the silicon-containing aromatic acetylene resin-based composite material may refer to the mass percentage of the fiber cloth in the resin-based composite material, and is preferably 5%-25%, for example, 15%.
[0038] The present invention also provides a method for preparing the aforementioned silicon-containing aromatic acetylene resin-based composite material, which comprises the following steps:
[0039] (1) mixing a resin solution containing the resin matrix with the hollow glass microspheres, evaporating the solvent, and drying to obtain a prepreg;
[0040] (2) Curing the prepreg.
[0041] In step (1), the solvent in the resin solution can be a conventional solvent capable of dissolving the resin matrix, preferably tetrahydrofuran.
[0042] In step (1), the mixing time is sufficient to mix the two evenly, preferably 2-6 hours, for example 4 hours.
[0043] In step (1), the drying temperature is preferably 70-90° C., such as 80° C. The drying time is preferably 3-5 hours, such as 4 hours.
[0044] When the silicon-containing aromatic acetylene resin-based composite material only contains the resin matrix and the hollow glass microspheres, in step (1), the mass percentage of the resin matrix in the resin solution can refer to the mass percentage of the resin matrix in the resin solution during the preparation of the composite material with phenolic resin, epoxy resin or silicone rubber as the resin matrix, preferably 25%-50%, for example 45%, more preferably 25%-35%.
[0045] When the silicon-containing aromatic acetylene resin-based composite material also contains chopped fibers, in step (1), the preparation of the prepreg is generally as follows: a resin solution containing the resin matrix, the hollow glass microspheres and the chopped fibers are mixed and dried. The mass percentage of the resin matrix in the resin solution can refer to the mass percentage of the resin matrix in the resin solution during the preparation of a composite material with a phenolic resin, an epoxy resin or a silicone rubber as a resin matrix, preferably 25%-50%, for example 45%, more preferably 29%-30%.
[0046] When the silicon-containing aromatic acetylene resin-based composite material also contains fiber cloth, in step (1), the preparation of the prepreg is generally as follows: S1, 12%-21% of the resin solution containing the resin matrix is impregnated into the fiber cloth to obtain prepreg I; S2, the remaining resin solution containing the resin matrix is mixed evenly with the hollow glass microspheres to obtain prepreg II; S3, a layer of the prepreg I and a layer of the prepreg II are stacked layer by layer, and dried.
[0047] In step S1, the mass percentage of the resin matrix in the resin solution can refer to the mass percentage of the resin matrix in the resin solution during the preparation of a composite material with phenolic resin, epoxy resin or silicone rubber as the resin matrix, and is preferably 45%-65%, such as 50%.
[0048] In step S1, the ratio of the resin solution used to soak the fiber cloth to the total resin solution is preferably 16%-20.8%, for example 20%.
[0049] In step S3, the layer-by-layer stacking method refers to a stacking method of repeatedly stacking a layer of the prepreg I, a layer of the prepreg II, a layer of the prepreg I, and a layer of the prepreg II.
[0050] In step S3, the drying temperature is preferably 75-85° C., such as 80° C. The drying time is preferably 3-5 hours, such as 4 hours.
[0051] In step (2), the mold used for curing can be preheated according to the conventional art before curing. The preheating temperature is preferably 120-170° C. The preheating time is preferably 1-2 hours.
[0052] Wherein, when the silicon-containing aromatic acetylene resin-based composite material further contains chopped fibers or fiber cloth, after the preheating and before the curing, preferably, the prepreg is pressurized, and the terminal pressure of the pressurization is 0.6-0.9 MPa.
[0053] In step (2), the curing temperature may be a conventional temperature in the art that can cure the resin, preferably 150-300°C, more preferably 170-260°C.
[0054] Preferably, the curing goes through the first stage, the second stage and the third stage in sequence, and the curing temperature of the second stage is higher than the curing temperature of the first stage, and the curing temperature of the third stage is higher than the curing temperature of the second stage. More preferably, the curing temperature of the first stage is 160-180°C (e.g., 170°C), the curing temperature of the second stage is 200-220°C (e.g., 210°C), and the curing temperature of the third stage is 240-260°C (e.g., 250°C). Further more preferably, the curing time of the first stage is 1.5-2.5h (e.g., 2h), the curing time of the second stage is 2-3h, and the curing time of the first stage is 4-5h.
[0055] In step (2), the curing time may be a conventional time in the art that allows the resin to cure, preferably 4-12 hours, more preferably 8-10 hours.
[0056] The present invention also provides a use of the aforementioned silicon-containing aromatic acetylene resin-based composite material as a thermal insulation material.
[0057] In the present invention, preferably, the silicon-containing aromatic acetylene resin-based composite material is used as an aerospace thermal insulation material.
[0058] Without violating the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0059] The reagents and raw materials used in the present invention are commercially available.
[0060] The positive progress of the present invention is that the silicon-containing aromatic acetylene resin-based composite material of the present invention can withstand a temperature of 500°C, has excellent mechanical properties, and has the two characteristics of low density and low thermal conductivity. Therefore, it can be used as a thermal insulation material in the fields of aerospace and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 is the TGA curve of the silicon-containing aromatic acetylene resin-based composite material obtained in Example 1;
[0062] Figure 2 This is the DMA curve of the silicon-containing aromatic acetylene resin-based composite material obtained in Example 4. DETAILED DESCRIPTION
[0063] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0064] In the following examples, the heat resistance of the obtained silicon-containing aromatic acetylene resin-based composite materials was analyzed by thermogravimetric analysis (TGA) and dynamic thermomechanical analysis (DMA). The thermogravimetric analysis used a TGA / DSC 1LF thermogravimetric analyzer from METTLER TOLEDO, Switzerland, with a heating rate of 10°C / min, a temperature range of 50-900°C, and a nitrogen flow rate of 60 mL / min; the dynamic thermomechanical analysis used a DMA1 thermogravimetric analyzer from METTLER TOLEDO, Switzerland. The experiment was carried out in a nitrogen atmosphere, using a "three-point bending" loading mode, a heating rate of 5°C / min, a temperature range of 50-500°C, and a frequency of 1 Hz.
[0065] In the following examples, the density of the obtained silicon-containing aromatic acetylene resin-based composite material was measured using an MH-124S electronic density test balance produced by Shenzhen Qunlong Instrument Equipment Co., Ltd., with 5 to 8 samples in each group tested according to standard GB / T 1463-2005, and the results were averaged.
[0066] In the following embodiments, the mechanical properties of the obtained silicon-containing aromatic acetylene resin-based composite materials were tested using a SANS CMT 4204 microcomputer-controlled electronic universal testing machine of Shenzhen Xinsansi Material Testing Co., Ltd. The compressive strength of the silicon-containing aromatic acetylene resin-based composite materials was tested according to GB / T 1448-2005 standard, the loading speed was 2 mm / min, and the sample was continuously loaded until it was damaged during the test. There were 5-10 samples in each group, and the results were averaged; the tensile strength of the silicon-containing aromatic acetylene resin-based composite materials was tested according to GB / T 1447-2005 standard, the loading speed was 2 mm / min, and the sample was continuously loaded until it was damaged during the test. There were 5-10 samples in each group, and the results were averaged.
[0067] In the following examples, the thermal conductivity of the silicon-containing aromatic acetylene resin-based composite material was tested by laser flash method using LFA447 laser thermal conductivity instrument produced by NETZSCH of Germany. Each group of samples had 3-4 samples and the results were averaged.
[0068] In the following embodiments, the unmodified silicon-containing aromatic acetylene resin is prepared by referring to the preparation method of paragraph
[0044] of the specification of patent document CN 102649838A; the model of the hollow glass microsphere is VS5500, and the manufacturer is 3M China Co., Ltd.; the carbon fiber is T700 carbon fiber of Toray Industries, Ltd. of Japan; the quartz glass fiber is B-type quartz fiber of Hubei Feilihua Quartz Glass Co., Ltd.; the carbon fiber cloth is T300 carbon fiber cloth of Toray Industries, Ltd. of Japan; the quartz glass fiber cloth is quartz fiber cloth of Hubei Feilihua Quartz Glass Co., Ltd.; and ethynyltriethoxysilane (TEOAS) is prepared by referring to patent US20120190549.
[0069] The specific operating parameters of the following examples are shown in Table 1.
[0070] Table 1 Operating parameters of each embodiment
[0071]
[0072] Example 1
[0073] The preparation method of the silicon-containing aromatic acetylene resin-based composite material is as follows:
[0074] 1. Preparation of hollow glass microspheres after surface treatment:
[0075] Step (1): 50 g of hollow glass microspheres are dispersed in 200 mL of treatment solution I and soaked for 1 hour, then washed with deionized water, separated into solid and liquid, until the filtrate is neutral, and dried in a vacuum oven at 100° C. to obtain hollow glass microspheres I; wherein the treatment solution I is prepared by 98 wt % concentrated sulfuric acid and 30 wt % hydrogen peroxide in a volume ratio of 3:1.
[0076] Step (2): dispersing the hollow glass microspheres I in 400 mL of the treatment solution II, adding a silane coupling agent, stirring at 40° C. for 4 h, separating the solid from the liquid, and drying at 100° C. for 12 h to obtain the hollow glass microspheres; wherein the treatment solution II is prepared from water, acetic acid and ethanol in a volume ratio of 1:2:9, and the mass of the silane coupling agent accounts for 2% of the mass of the hollow glass microspheres.
[0077] 2. Preparation of prepreg: dissolve the unmodified silicon-containing aromatic acetylene resin in a solvent to obtain a resin solution; then, add the above-mentioned surface-treated hollow glass microspheres, stir mechanically, evaporate the solvent, and dry in a vacuum oven to obtain the prepreg.
[0078] 3. Curing of prepreg: First, polish the mold and spray the release agent evenly on the mold surface, then place it in a vacuum oven for preheating, then pour the prepreg into the mold and keep it under vacuum for about 0.5h to remove air and solvent, until no bubbles appear within 3s, then transfer it to a high-temperature oven and cure it according to the curing procedure.
[0079] Example 2-3
[0080] The preparation method of the silicon-containing aromatic acetylene resin-based composite material is as follows:
[0081] 1. The preparation steps of the surface-treated hollow glass microspheres are the same as those in Example 1.
[0082] 2. Preparation of prepreg: dissolve bisphenol A dipropargyl ether and unmodified silicon-containing aromatic acetylene resin in a solvent to obtain a resin solution; then add the above-mentioned surface-treated hollow glass microspheres, stir mechanically, evaporate the solvent, and dry in a vacuum oven to obtain the prepreg.
[0083] 3. The curing steps of the prepreg are the same as those in Example 1.
[0084] Embodiment 4-6
[0085] The preparation method of the silicon-containing aromatic acetylene resin-based composite material is as follows:
[0086] 1. The preparation steps of the surface-treated hollow glass microspheres are the same as those in Example 1.
[0087] Preparation of surface-treated chopped fibers: Disperse the chopped fibers in acetone, perform ultrasonic cleaning, repeat for more than 3 times to remove the surface sizing agent, and dry them in a vacuum oven to obtain the chopped fibers.
[0088] 2. Preparation of prepreg: dissolve bisphenol A dipropargyl ether and unmodified silicon-containing aromatic acetylene resin in a solvent to obtain a resin solution; then add the above-mentioned surface-treated hollow glass microspheres and stir mechanically; then add the above-mentioned chopped fibers, mix well and disperse, and let it stand in a fume hood for 12 hours to remove the solvent; and dry in a vacuum oven to obtain.
[0089] 3. Curing of prepreg: First, polish the mold and spray the release agent evenly on the mold surface, then place it in a flat vulcanizer for preheating, then evenly spread the prepreg into the mold, pressurize the prepreg, and then cure it according to the curing procedure.
[0090] Example 7
[0091] The preparation method of the silicon-containing aromatic acetylene resin-based composite material is as follows:
[0092] 1. The preparation steps of the surface-treated hollow glass microspheres are the same as those in Example 1.
[0093] 2. Preparation of prepreg: dissolving an unmodified silicon-containing aromatic acetylene resin in a solvent to obtain a resin solution; taking a portion of the resin solution (see the proportion in Table 1) to impregnate a fiber cloth to obtain a prepreg I; adding the above-mentioned surface-treated hollow glass microspheres to the remaining resin solution, and uniformly mixing to obtain a prepreg II; then stacking the prepreg I and the prepreg II layer by layer, and drying to obtain; wherein, the layer-by-layer stacking method refers to a layer of prepreg I, a layer of prepreg II, a layer of prepreg I, and a layer of prepreg II, and such a stacking method is repeated continuously.
[0094] 3. The curing steps of the prepreg are the same as those in Example 4.
[0095] Example 8
[0096] The preparation method of the silicon-containing aromatic acetylene resin-based composite material is as follows:
[0097] 1. The preparation steps of the surface-treated hollow glass microspheres are the same as those in Example 1.
[0098] 2. Preparation of prepreg: dissolve bisphenol A dipropargyl ether and unmodified silicon-containing aromatic acetylene resin in a solvent to obtain a resin solution; the subsequent steps are the same as those in Example 7.
[0099] 3. The curing steps of the prepreg are the same as those in Example 4.
[0100] Effect Example 1
[0101] The silicon-containing aromatic acetylene resin-based composite material obtained in Example 1 was subjected to thermogravimetric analysis according to the above test method. The obtained TGA curve is as follows: Figure 1 As shown, Figure 1 The physical meaning represented by the ordinate in is the mass percentage of the silicon-containing aromatic acetylene resin-based composite material under each abscissa to the mass percentage of the initial silicon-containing aromatic acetylene resin-based composite material. Figure 1 It can be seen that in the range of 50-500°C, the weight loss is less than 1.63%. It can be seen that the silicon-containing aromatic acetylene resin-based composite material of the present invention can withstand a temperature of 500°C.
[0102] The silicon-containing aromatic acetylene resin-based composite material obtained in Example 4 was subjected to DMA analysis according to the above test method. The obtained DMA curve is as follows: Figure 2 As shown. Figure 2 It can be seen that within the range of 50-500°C, the common logarithmic value of the storage modulus and the loss factor remain substantially unchanged. It can be seen that the silicon-containing aromatic acetylene resin-based composite material of the present invention can withstand a temperature of 500°C.
[0103] Table 2 Effect data of each embodiment
[0104]
[0105] As can be seen from Table 2, the silicon-containing aromatic acetylene resin-based composite material of the present invention does not undergo glass transition in the range of 50-500°C, so it can be further known that it can withstand a temperature of 500°C, and has excellent mechanical properties, as well as the two characteristics of low density and low thermal conductivity. Therefore, it can be used as a thermal insulation material in the fields of aerospace and the like.
[0106] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A silicon-containing aromatic acetylene resin-based composite material, characterized in that: The silicon-containing aromatic acetylene resin-based composite material comprises a resin matrix and surface-treated hollow glass microspheres; The resin matrix is an unmodified silicon-containing arylacetylene resin and / or a modified silicon-containing arylacetylene resin; the modified silicon-containing arylacetylene resin is a silicon-containing arylacetylene resin modified with aryl dipropargyl ether, and the mass percentage of the aryl dipropargyl ether in the modified silicon-containing arylacetylene resin is w, 0<w≤50%; The mass percentage of the resin matrix in the silicon-containing aromatic acetylene resin-based composite material is 50%-75%; The mass percentage of the surface-treated hollow glass microspheres in the silicon-containing aromatic acetylene resin-based composite material is 25%-50%; The silicon-containing aromatic acetylene resin-based composite material contains chopped fibers and / or fiber cloth.
2. The silicon-containing aromatic acetylene resin-based composite material according to claim 1, characterized in that: The mass percentage of the resin matrix in the silicon-containing aromatic acetylene resin-based composite material is 50%-70%; and / or, the aromatic dipropargyl ether is one or more of bisphenol A dipropargyl ether, 4,4'-bisphenol fluorene dipropargyl ether and 4,4'-diphenyl ether dipropargyl ether; And / or, the mass percentage of the aryl dipropargyl ether in the modified silicon-containing aryl acetylene resin is 10%-30%; And / or, the mass percentage of the surface-treated hollow glass microspheres in the silicon-containing aromatic acetylene resin-based composite material is 30%-35%.
3. The silicon-containing aromatic acetylene resin-based composite material according to claim 1, characterized in that: The aromatic dipropargyl ether is bisphenol A dipropargyl ether.
4. The silicon-containing aromatic acetylene resin-based composite material according to claim 1, characterized in that: The surface-treated hollow glass microspheres are prepared by the following treatment method: (1) treating the hollow glass microspheres to increase the hydroxyl content on their surfaces; and (2) treating with a silane coupling agent to connect one end of the silane coupling agent to the hydroxyl groups on the surfaces of the hollow glass microspheres.
5. The silicon-containing aromatic acetylene resin-based composite material according to claim 4, characterized in that: The operation of step (1) is as follows: the hollow glass microspheres are dispersed in the treatment solution I and soaked for 0.5-2 h, then washed with deionized water, separated into solid and liquid until the filtrate is neutral, and dried to obtain the hollow glass microspheres I; wherein the treatment solution I is prepared by 90wt%-98wt% concentrated sulfuric acid and 20wt%-40wt% hydrogen peroxide in a volume ratio of (2-4):
1.
6. The silicon-containing aromatic acetylene resin-based composite material according to claim 5, characterized in that: in, The model of the hollow glass microsphere is VS5500.
7. The silicon-containing aromatic acetylene resin-based composite material according to claim 5, characterized in that: The mass ratio of the hollow glass microspheres to the volume of the treatment solution I is 1:(3-5), in units of g / mL.
8. The silicon-containing aromatic acetylene resin-based composite material according to claim 5, characterized in that: The drying temperature is 90-110°C.
9. The silicon-containing aromatic acetylene resin-based composite material according to claim 5, characterized in that: The operation of step (2) is as follows: dispersing the hollow glass microspheres I in the treatment solution II, adding a silane coupling agent, stirring at 25-65° C. for 2-6 hours, separating the solid and the liquid, and drying; wherein the treatment solution II is prepared from water, acetic acid and ethanol in a volume ratio of 1:(1-3):(7-11), and the mass of the silane coupling agent accounts for 0.5%-5% of the mass of the hollow glass microspheres.
10. The silicon-containing aromatic acetylene resin-based composite material according to claim 9, characterized in that: The mass ratio of the hollow glass microspheres to the volume of the treatment solution II is 1:(7-9), in g / mL; And / or, the silane coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane and ethynyltriethoxysilane; And / or, the drying temperature is 90-110°C; And / or, the drying time is 10-14 hours.
11. The silicon-containing aromatic acetylene resin-based composite material according to claim 1, characterized in that: The length of the chopped fibers is 5-50 mm.
12. The silicon-containing aromatic acetylene resin-based composite material according to claim 1, characterized in that: The length of the chopped fibers is 20-40 mm.
13. The silicon-containing aromatic acetylene resin-based composite material according to claim 11, characterized in that: The chopped fibers are one or more of high-silica glass fibers, quartz glass fibers and carbon fibers; And / or, the chopped fibers are surface-treated chopped fibers, and the treatment method is as follows: dispersing the chopped fibers in an acetone solution, ultrasonically cleaning for 1-3 h, repeating for more than 3 times to remove the surface sizing agent, and drying; And / or, the mass percentage of the chopped fibers in the silicon-containing aromatic acetylene resin-based composite material is 5%-25%; And / or, the fiber cloth is one or more of high-silica glass fiber cloth, quartz glass fiber cloth and carbon fiber cloth; And / or, the mass percentage of the fiber cloth in the silicon-containing aromatic acetylene resin-based composite material is 5%-25%.
14. The silicon-containing aromatic acetylene resin-based composite material according to claim 13, characterized in that: The ultrasonic cleaning time is 1-1.5 h; And / or, the drying temperature is 85-95°C; And / or, the drying time is 3-5h.
15. A method for preparing a silicon-containing aromatic acetylene resin-based composite material according to any one of claims 1 to 14, characterized in that: It includes the following steps: (1) mixing a resin solution containing the resin matrix, the hollow glass microspheres, the chopped fibers and / or the fiber cloth, evaporating the solvent, and drying to obtain a prepreg; (2) Curing the prepreg.
16. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 15, characterized in that: In step (1), the solvent in the resin solution is tetrahydrofuran.
17. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 15, characterized in that: The silicon-containing aromatic acetylene resin-based composite material also contains chopped fibers. In step (1), the prepreg is prepared as follows: a resin solution containing the resin matrix, the hollow glass microspheres and the chopped fibers are mixed and dried.
18. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 17, characterized in that: The mass percentage of the resin matrix in the resin solution is 25%-50%.
19. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 17, characterized in that: The mass percentage of the resin matrix in the resin solution is 29%-30%.
20. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 15, characterized in that: The silicon-containing aromatic acetylene resin-based composite material also contains fiber cloth. In step (1), the prepreg is prepared as follows: S1, 12%-21% of the resin solution containing the resin matrix is impregnated into the fiber cloth to obtain prepreg I; S2, the remaining resin solution containing the resin matrix is evenly mixed with the hollow glass microspheres to obtain prepreg II; S3, a layer of the prepreg I and a layer of the prepreg II are stacked layer by layer, and dried.
21. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 20, characterized in that: In step S1, the mass percentage of the resin matrix in the resin solution is 45%-65%; And / or, in step S1, the proportion of the resin solution used to soak the fiber cloth to the total resin solution is 16%-20.8%; And / or, in step S3, the drying temperature is 75-85°C; And / or, in step S3, the drying time is 3-5 hours.
22. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 15, characterized in that: In step (2), the mold used for curing is preheated before curing; And / or, in step (2), the curing temperature is 150-300°C.
23. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 22, characterized in that: The preheating temperature is 120-170°C; And / or, the preheating time is 1-2h.
24. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 22, characterized in that: After the preheating and before the curing, the prepreg is pressurized, and the terminal pressure of the pressurization is 0.6-0.9 MPa.
25. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 22, characterized in that: The curing temperature is 170-260°C.
26. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 22, characterized in that: The curing sequentially goes through a first stage, a second stage and a third stage, and the curing temperature of the second stage is higher than the curing temperature of the first stage, and the curing temperature of the third stage is higher than the curing temperature of the second stage.
27. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 26, characterized in that: The curing temperature of the first stage is 160-180°C, the curing temperature of the second stage is 200-220°C, and the curing temperature of the third stage is 240-260°C.
28. The method for preparing the silicon-containing aromatic acetylene resin-based composite material according to claim 27, characterized in that: The curing time of the first stage is 1.5-2.5 hours, the curing time of the second stage is 2-3 hours, and the curing time of the third stage is 4-5 hours.
29. Use of the silicon-containing aromatic acetylene resin-based composite material according to any one of claims 1 to 14 as a thermal insulation material.
30. Use of the silicon-containing aromatic acetylene resin-based composite material as claimed in claim 29 as a thermal insulation material, characterized in that: The silicon-containing aromatic acetylene resin-based composite material is used as an aerospace thermal insulation material.
Citation Information
Patent Citations
Bisphenol benzoxazine modified silicon-contained aryne resin and preparation method thereof
CN102649838A
6-amino-2-substituted-5-vinylsilylpyrimidine-4-carboxylic acids and esters and 4-amino-6-substituted-3-vinylsilylpyridine-2-carboxylic acids and esters as herbicides
US20120190549A1
AIN (aluminium nitride) / silicon-containing arylacetylene resin composite material as well as preparation method and application thereof
CN108395704A